2017
DOI: 10.1080/1062936x.2017.1311941
|View full text |Cite
|
Sign up to set email alerts
|

Application of IATA – A case study in evaluating the global and local performance of a Bayesian network model for skin sensitization

Abstract: The information characterizing key events in an Adverse Outcome Pathway (AOP) can be generated from in silico, in chemico, in vitro and in vivo approaches. Integration of this information and interpretation for decision making are known as integrated approaches to testing and assessment (IATA). One such IATA was published by Jaworska et al., which describes a Bayesian network model known as ITS-2. The current work evaluated the performance of ITS-2 using a stratified cross-validation approach. We also characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All wrong predictions were caused by misclassifications into a directly neighboring class. A recent study showed for version 2 of this ITS that the TIMES-SS (a commercial product) can be substituted by the structural alerts set implemented in the protein binding for skin sensitization profiler of the OECD QSAR toolbox (which is free software and the structural alerts are related to those covered by TIMES-SS) without a substantial decrease in prediction accuracy (Fitzpatrick and Patlewicz 2017). Luechtefeld et al (2015) trained dose-informed random forest/hidden Markov classification models on categorical LLNA data compiled for 145 substances (mainly derived from the Jaworska data set; see section "Data sets").…”
Section: Computational Methods Used In Combination With Nonanimal Tesmentioning
confidence: 99%
“…All wrong predictions were caused by misclassifications into a directly neighboring class. A recent study showed for version 2 of this ITS that the TIMES-SS (a commercial product) can be substituted by the structural alerts set implemented in the protein binding for skin sensitization profiler of the OECD QSAR toolbox (which is free software and the structural alerts are related to those covered by TIMES-SS) without a substantial decrease in prediction accuracy (Fitzpatrick and Patlewicz 2017). Luechtefeld et al (2015) trained dose-informed random forest/hidden Markov classification models on categorical LLNA data compiled for 145 substances (mainly derived from the Jaworska data set; see section "Data sets").…”
Section: Computational Methods Used In Combination With Nonanimal Tesmentioning
confidence: 99%
“…29 Other computational approaches, beyond the ab initio risk assessment consideration, that utilise and extend the AOP framework are the development of Integrated Assessment and Testing Approaches (IATAs). 13,18,[30][31][32][33][34][35][36][37][38] The Links Between in Silico Models and the Different Steps of an AOP Figure 1 illustrates that models, or in silico approaches, may potentially be utilised at all stages of the AOP to provide knowledge and information (it should be noted that the structure of the generic AOP shown in Figure 1 is illustrative only and many AOPs do not include exposure or proceed to the ecosystem level). There are many purposes to the use of models within the AOP framework; these include:…”
Section: Introductionmentioning
confidence: 99%
“…For some human adverse outcomes (e.g., skin sensitization), various mechanistically informed DAs have already been developed based on AOPs (AOP-informed IATA). AOP-informed IATA for skin sensitization incorporates methods anchored against KE identified in the published AOP in conjunction with non-testing approaches ((Q)SAR, read-across) (Patlewicz et al, 2014;Fitzpatrick and Patlewicz, 2017;OECD, 2016b).…”
Section: Towards An Ontology-based Concept Of Future Dnt Testingmentioning
confidence: 99%